Challenges, Benefits and Considerations of Transitioning Disease Classification and Codification to ICD-11: Tantangan, Manfaat dan Pertimbangan Transisi Klasifikasi dan Kodifikasi Penyakit Menuju ICD-11 - Perwirani, Resia; Hidayat, Andra Dwitama; Raharjo, Untoro Dwi (Procedia of Engineering and Life Science, 2025)
ICD-11 was developed to address the limitations of ICD-10, adapting to advances in medicine and technology. ICD-11 has not been implemented in Indonesia due to the absence of supporting regulations that enforce the use of ICD-11 as a disease coding guideline to replace ICD-10. This study analyses information related to the benefits, challenges and considerations of implementing ICD-11 in the form of a narrative literature review conducted using the PRISMA framework. The databases used were Google Scholar, Pubmed, ScienceDirect and Scopus. Article search keywords used the SPICE research question framework. Inclusion criteria included articles published within 2019-2024 in English or Indonesian. Article screening was conducted using the Rayyan.ai tool, followed by critical appraisal using the MMAT instrument with a cut-off point of 80%. We obtained 5,813 articles from the database. A total of 5,776 articles were excluded, 4 articles were duplicated, leaving 13 articles selected for extraction and analysis. ICD-11 has many benefits, including a more complete list of diagnoses and health-related problems, from the update of classification data in each organ system/disease group category to the inclusion of new categories. ICD-11 also has a “post- coordination” feature and cluster codes allow for more specific diagnosis codes. One of the barriers to the implementation of ICD-11 is that there are other classification guidelines in some particular diseases that overlap with ICD-11, for example in the classification of mental illness and CHD. The implementation of SNOMED-CT, which is expected to go in parallel with the use of ICD-11, requires a Common Ontology to map the semantics of each system’s terminology. Successful implementation requires policy support, effective training, improved clinical documentation, and promotion so that ICD-11 can be implemented effectively, ensuring relevance and usefulness in various health fields.